Smart System Side Slip Tester Results Accuracy Improvement Using Exponential Filter - Arief Marwanto; Riky Maulana Firdaus; Muhammad Qomaruddin; Deshinta Arrova Dewi; Tri Basuki Kurniawan; Imam Much Ibnu Subroto (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
According to Article 6, Paragraph 1, of Law No. 55 of 2012 Concerning Cars, cars that are not roadworthy are particularly harmful for the safety of passengers and other road users. The front wheel ring, which has a significant impact on the safety of the motorized vehicle, is one of the technical requirements for roadworthiness. The front wheel pins make sure the car can go straight, which is related to the steering system's safety and has an impact on fuel economy. Through routine testing at the motor vehicle testing facility owned by the Transportation Service, the front wheel valve examination is performed using a front wheel blade test tool known as the Side Slip Tester. Previously, a lot of the automobile test equipment used at various test facilities was impractical and inaccurate. The construction of a smart system for evaluating wheel blades on cars is covered in this study, along with the implementation of an exponential filter to improve and lower the noise in sensor readings of ADC signals. By comparing the readings of the manufactured tool with a calibrated dial indicator, tests and calibrations are performed. The graph shows that the response to the input signal is quick and excellent for noise filtering, so based on the results of the exponential filter test, 0.2 is the ideal weight for the ADC reading filter. The 9 mm side slip bench shear test yields a maximum error result of 3% following tool calibration.